Rutting season in domestic reindeer - weight development and androgen variation - Inga, Berit (Rangifer, 1984)
In order to describe weight development and androgen variation in reindeer bulls of the forest type during the rutting season data were collected on carcass weight, weight of m sterno cepbalicus and omentum majus. Blood samples were taken for analysis of testosterone. Sampling and material collection was carried out during 22/8 - 4/11, 1983 (N=100) in the area around Arvidsjaure (65,5° N lat) in Sweden. The concentration of testosterone during the pre-rut (22/8 - 22/9) was an average of ~10 - 25 ng/ml plasma for the oldest creatures, while 2 1/2 - 3 1/2 year olds was ~5 - 10 ng/ml plasma. During the most active rutting period (27/9 - 7/10) the testosterone concentration was at highest level, which is shown by two bulls (one 5 1/2 years old and one older) who each had ~170 ng/ml plasma. After the rutting period the testosterone concentration for all age groups lay at ~1 ng/ml plasma. The weight of m sterno cepbalicus demonstrated the clearest correlation with testosterone. This correlation was particulary evident in the older bulls (3 1/2 years and older) while it was completely missing in the youngest. The muscle showed an regular weight increase, both in absolute and relative figures. In the oldest bulls the muscle weight doubled from the pre-rut to the most active rutting period. Brunstperioden hos tamren - viktutveckling och androgen variation. Abstract in Swedish / Sammanfattning: For att beskriva viktutveckling och androgenvariation hos sarvar av skogsren under brunstperioden insamlades uppgifter om slaktvikt, vikt hos m stemo cephalicus och omentum majus. Blodprover togs for analys av testoteron. Materialinsamlingen skedde under tiden 22/8 - 4/11 1983 (N= 100) runt Arvidsjaure (65,5°N lat) Sverige. Testosteronkoncentrationen under forbrunsten (22/8 - 22/9) var hos de aldsta i medeltal ~10-25 ng/ml plasma, medan 2 1/2 - 31/2 åringars halt var ~5 - 10 ng/ml plasma. Under stimtiden (27/9 - 7/10) var testosteronkoncentrationen hogst, vilket framgår av att två sarvar (en 5 1/2 år och en aldre) hade ~170 ng/ml plasma vardera. Efter brunstperioden var testosteronkoncentrationen låg i samtliga åldersklasser, ~1 ng/ml plasma. Vikten hos m stemo cephalicus visade det klaraste sambandet med androgen. Detta samband fanns sårskilt hos aldre sarvar (3 1/2 år och aldre) medan det saknades helt hos de yngsta. Muskeln visade en entydig viktokning både i absoluta och relativa tal. Hos de aldsta sarvarna fordubblades muskelns vikt från forbrunst till stimtid. Porojen kiima-aika - painonkehitys ja androgenin vaihtelu. Abstract in Finnish / Yhteenveto: Urosporojen painonkehityksen ja androgenin vaihtelun kuvailemiscksi kiima-aikana kerâttiin tietoja teuraspainosta, m sterno cephalicus - ja omentum majus-painosta. Verikokeita otettiin testostcronin analyysia varten. Aineiston keråys (N = 100) tapahtui 22/8 - 4/11 1983 valisenâ aikana Arvidsjauren seuduilla (65,5 °P. lev.), Ruotsissa. Testosteronikonsentraatio kiiman alkuvaiheessa (22/8 - 22/9) oli vanhimmilla keskimààrin ~ 10-25 ng/ml plasma, kun taas 21/2 - 31/2 - vuotisilla arvo oli ~ 5-10 ng/ml plasma. Kiima-aikana (27/9 - 7/10) oli testosteronikonsentraatio korkein, joka ilmenee siitâ, etta kahdella urosporolla (5 Vi v. ja yksi vanhempi) oli molemmilla ~ 170 ng/ml plasma. Kiima-ajan jalkeen oli testosteronikonsentraatio kaikilla ikaluokilla alhainen, ~ 1 ng/ml plasma. M sterno cephalicus-pzino osoitti selvâsti yhteyttâ androgenin kanssa. Tama yhteys ilmeni erikoisesti vanhemmilla urosporoilla (3 1/2 v. ja vanhemmat), kun se sitåvastoin puuttui nuorimmilla. Lihas osoitti yksiselitteistå painonlisåystå seka absoluuttisessa ettå relatiivisessa luvussa. Vanhimpien urosporojen lihaspaino kaksinkertaistui kiiman alkuvaiheesta kiima-aikaan.